Metabolic Responses to Excess Manganese in Legumes: Variations in Nitrogen Compounds in Canavalia ensiformis (L.) DC and Cajanus cajan (L.) Millsp - Mendes, Thalita Fischer Santini [UNESP]; Ferreira, Tassia Caroline [UNESP]; Bomfim, Nayane Cristina Pires [UNESP]; Aguilar, Jailson Vieira [UNESP]; de Camargos, Liliane Santos [UNESP] (Wiley, 2024)
Manganese (Mn) is crucial as a trace element for plant metabolism, but high concentrations in soil can induce symptoms of toxicity. This study aimed to evaluate the metabolism of nitrogen compounds and biomass production in Canavalia ensiformis and Cajanus cajan, clarifying the effects of this metal on nitrogen metabolism. The soil was treated with Mn concentrations of 80, 100, 120, 140, and 160 mg kg−1. Differential responses were observed in the metabolism of nitrogenous compounds between species. C. cajan affected nitrogen metabolism in shoots, roots, and nodules, with significant variations in amino acids, total soluble proteins, ureides, and root biomass concentration. In contrast, C. ensiformis showed stability in the concentrations of compounds, mainly ureides, and proteins, even with increasing doses of Mn in the soil. These findings highlight the importance of nitrogen metabolism in legumes studied as a key aspect for understanding their Mn tolerance mechanisms in soil.
Keywords: jack bean; legumes; physiology; pigeon pea; trace element